TV Series: A Form of Adaptation to The Contemporary Media Condition - Angela Maiello (Rivista di Estetica, 2023)
The article connects the forms of contemporary TV series with the narrative and participatory logics of contemporary media. In particular, the author proposes to consider the wide diffusion and popularity of TV series as a form of response and adaptation to the contemporary media condition. The article proposes an analysis of the ways in which the human instinct for storytelling finds form in contemporary participatory media practices. This reflection is situated within the broader debate on post-cinema and the ways in which new technologies have transformed cinema and audiovisual products. This theoretical perspective is related to the well-known twentieth-century philosophical reflection on the status of narration. TV series, therefore, are a response to the “call for concordance” (Ricœur) that is nowadays more evident than ever. Yet there seems to be a sort of paradox here, that characterises the TV series aesthetic experience: in the process of accomplishing this concordance, by creating solid and unitary world, TV series adapt that transmedia aesthetic (Jenkins) of fragmentation that is typical of contemporary media logic. At the end the author discusses some examples.